Health and Environmental Pollution: A Literature Review - Yuniarti, Elsa; Exposto, Levi Anatolia S.M.; Dewata, Indang; Nugraha, Fitra Arya Dwi; Alfitri, Alfitri (UI Scholars Hub, 2024)
This study aimed to review various studies focusing on pollution that could adversely affect health, including sources, types, and mitigation efforts. The data used were obtained through a search on the Scopus website using the keywords